Morphological Characteristics of Ectomycorrhizas on Merbau [Intsia bijuga (Colebr.) O. Kuntze] - JULIUS DWI NUGROHO; IRDIKA MANSUR; AGUS PURWITO; ENDANG SUHENDANG (Bogor Agricultural University, Indonesia, 2010)
Merbau [Intsia bijuga (Colebr.) O. Kuntze] is one of valuable timber tree in south-east Asia which has been known having ectomycorrhizae (EcM) though being ignored. Identification of the ectomycorrizae is prime important for being basis of further studies. This study investigated the EcM fungi associated with Merbau by using both sporocarp morphology and EcM morphotypes. Morphological characters of sporocarps and basidiocarps of the fungi and EcM morphotypes obtained from seedlings and trees from natural and plantation stands of merbau, as well as from nurseries were compared to the description of those resulted from baiting method. Only one species of ectomycorrhizal fungus was found associated with merbau [Intsia bijuga (Colebr.) Kuntze] which has not been described yet. The fungus formed mycorrhizae with monopodial pinnate branching. The fungus was identified belonging to the genus of Scleroderma. The fungus was more common to occur beneath merbau seedlings than trees. The sporocarps may be yielded under greenhouse condition and could be cultured in MMN agar media, thus it facilitates to the production of inoculums used for further studies.